Challenges of Remote Working and How to Overcome The Challenge - Dwi Amalia, Ratih; Ikbal Sonuari, Mochammad; Sabrina Sasamu, Yetti (PT Konsuli Corpora Indonesia, 2025)
The COVID-19 pandemic has brought about a significant shift in the way people work, with remote working becoming a prevalent solution. Remote working, while beneficial in terms of flexibility and reduced commute times, presents several challenges, including difficulty in coordinating with coworkers, blurred boundaries between work and home life, and issues related to multitasking. This study examines the impact of remote working on employees, highlighting both the positive and negative aspects. It emphasizes that while remote working can provide increased flexibility, quality time with family, and improved comfort, it also creates obstacles such as decreased morale and work-life balance challenges. The study also discusses the role of telecommuting in urban planning and transportation, noting its potential to reduce traffic congestion and contribute to environmental sustainability. Through this analysis, the study seeks to provide a comprehensive understanding of remote working's implications, its future role in the workforce, and strategies to overcome the challenges it presents.